Efektivitas Implementasi Program Bantuan Rumah Tidak Layak Huni bagi Masyarakat Berpenghasilan Rendah di Kabupaten Agam - Tika, Sucia Angelia (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
Law Number 1 of 2011 recognizes the basic rights of every Indonesian citizen to have a decent place to live. Agam Regency itself has challenges such as uninhabitable houses and slums that arise due to economic problems, unemployment, and low income. To overcome this, the government implemented a home improvement assistance program for low-income communities. This study aims to analyze the effectiveness of the implementation of the Uninhabitable House Improvement Assistance Program (RTLH) in Agam Regency, especially for low-income communities. The method used is a qualitative descriptive approach, which explores the suitability of targets, benefits, desired changes, program policies, implementation and supervision, and availability of resources. Data were obtained through interviews with beneficiaries, the government, and related stakeholders. The results of the study show that the RTLH improvement assistance program has been well realized from 2019 to 2022, with 2,045 housing units receiving assistance. The RTLH policy is designed to meet the needs of low-income people and involve them in the renovation process. However, there are still challenges faced in the form of budget constraints, uneven distribution of materials, and supervision dominated by the government as well as social jealousy among the community.